2016
DOI: 10.4028/www.scientific.net/msf.845.138
|View full text |Cite
|
Sign up to set email alerts
|

First Principles Study of the Structural and Magnetic Properties of Cr-Doped Ni<sub>1.75</sub>Co<sub>0.25</sub>Mn<sub>1.5</sub>In<sub>0.5</sub> Heusler Alloys

Abstract: In this work, the structural and magnetic properties of Cr – doped Ni1.75Co0.25Mn1.5In0.5 Heusler alloys are investigated by using the density functional theory calculations. The chemical disorder is treated by the 16-atom supercell approach. Three compositions with substitution of 6.25 %, 12.5 %, and 18.75% Cr for Mn are taken into consideration. The formation energy, magnetic moments and lattice parameters depending on the Cr content are found. It is shown that compositions with 6.25% and 12.5% of Cr are ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
(10 reference statements)
1
5
0
Order By: Relevance
“…Figure shows the magnetocaloric effect of the alloy Ni 45 Co 5 Mn 32 Cr 5 In 13 with an adiabatic temperature change of nearly 10 K . This is a record value for Heusler alloys and is close to the Δ T ad =12.9 K value of Fe–Rh and 9.2 K for Fe 49 Rh 51 upon the first application of a magnetic field of Δ μ 0 H =1.9 T, which remains as high as 6.2 K during cycling in an alternated field of the same magnitude .…”
Section: Magnetostructural Phase Transition Of Rapidly Quenched Heuslsupporting
confidence: 59%
See 2 more Smart Citations
“…Figure shows the magnetocaloric effect of the alloy Ni 45 Co 5 Mn 32 Cr 5 In 13 with an adiabatic temperature change of nearly 10 K . This is a record value for Heusler alloys and is close to the Δ T ad =12.9 K value of Fe–Rh and 9.2 K for Fe 49 Rh 51 upon the first application of a magnetic field of Δ μ 0 H =1.9 T, which remains as high as 6.2 K during cycling in an alternated field of the same magnitude .…”
Section: Magnetostructural Phase Transition Of Rapidly Quenched Heuslsupporting
confidence: 59%
“…2018 Wiley-VCH Verlag GmbH &Co. KGaA,W einheim Figure 11 shows the magnetocaloric effect of the alloy Ni 45 Co 5 Mn 32 Cr 5 In 13 with an adiabatic temperature change of nearly 10 K. [17,59] This is ar ecord value for Heusler alloys and is close to the DT ad = 12.9 Kv alue of Fe-Rh [60,61] and 9.2 K for Fe 49 Rh 51 upont he first application of am agnetic field of Dm 0 H = 1.9 T, which remainsa sh igh as 6.2 Kd uring cycling in an alternated field of the same magnitude. [62] It has been shown that am agnetic state changeo fR hb etween antiferromagnetism (with aR hm omento f0m B )a nd ferromagnetism ( % 0.9 m B ), accompanied by as ignificant change in electronic structure,c ombinea st he main origin of the metamagnetic transition.…”
Section: Magnetostructural Phase Transition Of Rapidly Quenched Heuslmentioning
confidence: 99%
See 1 more Smart Citation
“…The model parameters for Ni 45 Co 5 Mn 37 In 13 microwires and coolant (water) were taken by analogy with Refs. [3,10,11]. Note that we consider the composition, which is similar to Ni 45.2 Mn 36.7 In 13 Co 5.1 [3].…”
Section: Resultsmentioning
confidence: 99%
“…Other remarkable features like the magnetic shape‐memory and magnetocaloric effects have recently been highlighted by Planes et al The isothermal entropy and and adiabatic temperature changes associated with the magnetostructural transition can be evaluated by Monte Carlo simulations using ΔSmagtrue(T,Htrue)=μ00HdH(MT)H, ΔTadtrue(T,Htrue)=TΔSmagtrue(T,Htrue)Ctrue(T,Htrue). Figure shows the magnetocaloric effect of the alloy Ni 45 Co 5 Mn 32 Cr 5 In 13 with an adiabatic temperature change of nearly 10 K . This is a record value for Heusler alloys and is close to ΔTad=12.9 K of Fe–Rh and 9.2 K for Fe 49 Rh 51 on the first application of a magnetic field of Δμ0H=1.9 T which remains as high as 6.2 K during the cycling in alternated field of the same magnitude .…”
Section: Magnetostructural Phase Transition Of Rapidly Quenched Heuslmentioning
confidence: 95%